Penerapan Metode Pembelajaran Drill untuk Meningkatkan Hasil Belajar Praktikum Akuntansi Siswa SMK Negeri 1 Seririt, Kabupaten Buleleng - Suantara, I Gusti Bagus Ari Setia; Meitriana, Made Ary (Universitas Pendidikan Ganesha, 2023)
Accounting learning requires an understanding of the concepts and stages in each material. The choice of method must be considered in order to achieve the learning objectives. The method used in learning accounting in class XI Accounting II before the action is a discussion method, while learning accounting is not only studying the theory. Lack of practice questions is given to students, which makes students not understand the concepts and stages in each material, which causes cognitive and psychomotor learning outcomes of accounting practicum students of class XI Accounting II to still be low. This study aims to determine the application of the drill learning method in improving the learning outcomes of accounting practicum students at SMK Negeri 1 Seririt. This research is classroom action research (CAR) conducted in class XI Accounting II by using descriptive statistical analysis to describe the learning outcomes of accounting practicum students of XI Accounting II. The results showed an increase in learning outcomes in each cycle. In the first cycle, cognitive learning outcomes increased 3.85%, and psychomotor increased 41.18%. The second cycle of cognitive learning outcomes increased by 11.11%, and psychomotor increased by 20.83%. So it can be concluded that the application of the drill learning method can improve the learning outcomes of accounting practicum students at SMK Negeri 1 Seririt.